CURRICULUM MANAGEMENT WITH A BLOCK SYSTEM LEARNING SCHEDULE FOR TEACHING FACTORY LEARNING IMPROVEMENT (TEFA) AT SMKN 1 SANGATTA UTARA - Sukamti Sukamti; Haeruddin Haeruddin; Akhmad Akhmad (RADJA PUBLIKA, 2025)
Vocational schools as vocational education institutions are expected to be able to organize practical learning processes that are relevant to the business world and the industrial world (DUDI). One of the approaches that is now developing in bridging the gap between the world of education and industry is the implementation of the Teaching Factory (TeFa). It is important to examine effective curriculum management with a block system to support Teaching Factory learning optimally. This study uses a qualitative approach with a descriptive method. Data was obtained by interviews, observations, and documentation collection. Data collection techniques use interviews, document checks, and observations. The research site of SMKN 1 Sangatta Utara in June 2025. Data collection techniques with purposing sampling techniques with respondents principals, vice principals in the field of curriculum and all heads of expertise competencies. The analysis used the interactive analysis model of Miles and Huberman (1984) which included the first stage of data reduction, data presentation and conclusion drawn. The validity of the research results is triangulated, namely comparing the results of several data collection techniques. The results of the research are curriculum management planning with the Block system learning schedule at SMKN 1 Sangatta carried out in grades X and XI, class XII is not applied to the Block system because it is more focused on preparing for the Final Assessment of Education Units and USK. The organization of curriculum management with the responsibility of the principal, coordinated by the vice principal for curriculum and assisted by curriculum staff, daily picket teachers, heads of expertise competencies and report operators. The implementation of the block system learning schedule is effective in improving TeFa learning in class XI, for X it has not been effective because it is still the basic skill competency that has not yet been targeted for the production of goods/services. Class XII is also ineffective as a block system learning schedule because it focuses on preparing for the Final Assessment of the Education Unit and the Competency Certification Test. Supervision of the block system learning schedule carried out by picket teachers, deputy principals for curriculum and school principals is not effective because some daily picket teachers do not really go around the classroom.